1955
DOI: 10.1111/j.1651-2227.1955.tb04287.x
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Agenesis of the Spleen on the Pathogenesis of Conotruncus Anomalies in Childhood

Abstract: Six embryos measuring 9–12 mm in greatest length have been shown by the writer to contain early splenic primordia in the left aspect of the dorsal mesogastrium. Their ovulation age is estimated to be 31–36 days. Temporal relations of splenic formation to conotruncus septation and division of the A‐V canal have been discussed. This last is divided before septation of the conotruncus is completed. The author has shown that early splenic primordia exist at the time of fusion of the A‐V canal cushions. At the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
1
3

Year Published

1963
1963
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(58 citation statements)
references
References 0 publications
0
54
1
3
Order By: Relevance
“…Asplenia can be functional as in sickle cell anaemia, acquired after trauma or surgery, or congenital (see Table 1). Congenital asplenia often occurs in the context of a recognised malformation syndrome: the Ivemark syndrome, also called asplenia syndrome (OMIM 208530) [12,20]. In this syndrome, malformations arise as lateralisation defects of organs in the thorax and the abdomen, now classified as situs abnormalities or heterotaxia syndromes with or without cardiac abnormalities, which are clinically and genetically heterogeneous conditions [1].…”
Section: Introductionmentioning
confidence: 97%
“…Asplenia can be functional as in sickle cell anaemia, acquired after trauma or surgery, or congenital (see Table 1). Congenital asplenia often occurs in the context of a recognised malformation syndrome: the Ivemark syndrome, also called asplenia syndrome (OMIM 208530) [12,20]. In this syndrome, malformations arise as lateralisation defects of organs in the thorax and the abdomen, now classified as situs abnormalities or heterotaxia syndromes with or without cardiac abnormalities, which are clinically and genetically heterogeneous conditions [1].…”
Section: Introductionmentioning
confidence: 97%
“…Ivemark (1955), reviewing 55 reported cases of splenic agenesis and 14 new serial cases from necropsy records, found that (1) 97 per cent had cono-truncal malformations (see Table IV); (2) that 56 of the 58 with an adequate description (970 O) had malformations of the region of the atrio-ventricular valve, a common A-V ostium in 79 per cent (with cor biloculare in 48 per cent) and mitral or tricuspid atresia in others; and (3) 85 per cent had some degree of situs inversus. The form of this was varied and in his tables he includes 23 as dextrocardia and 36 as isolatedlxvocardia.…”
Section: E+mentioning
confidence: 99%
“…Non-visualization of the spleen, both, with the 99mTcSc scan and the abdominal ultrasound indicated an anatomical asplenic state, acquired or congenital. Congenital asplenia (Ivemark syndrome) is a rare association of agenesis of the spleen with cyanotic congenital cardiac disease and malposition and nondevelopment of the abdominal viscera (abdominal heterotaxy) [2]. Since our patient had neither of these anomalies, Ivemark syndrome can be ruled out.…”
Section: Discussionmentioning
confidence: 93%